Distribution and Antifungal Susceptibility Pattern of Candida species at a Tertiary Hospital in Malaysia - Mohamed, NA; Hussin, H; Zaini, AB; Siva Gowri a/p Pathmanathan (J Infection Developing Countries, 2024)
Indexed by WOS/Scopus/ERA